Confucian Harmony in Dialogue with African Harmony: A Response - Li, Chenyang (2017)
Engaging in dialogue with African philosophy, I respond to questions raised by Thaddeus Metz on characteristics of Confucian philosophy in comparison with African philosophy. First, in both Confucian philosophy and African philosophy, harmony/harmonization and self-realization coincide in the process of person-making. Second, Confucians accept that sometimes it is inevitable to sacrifice individual components in order to achieve or maintain harmony at large scales; the point is how to minimize such costs. Third, Confucians give family love a central place in the good life before extend love to the rest of the world. Fourth, the Confucian philosophy of gender equality is based on appropriate division of labor consistent with its yin-yang philosophy, rather than equal split of power in the family. Fifth, in the Confucian view, hierarchy and harmony do not necessarily contradict each other, though hierarchy is not essential to all forms of harmony. The two can co-exist.